The acceptability of TV-based game platforms as an instrument to support the cognitive evaluation of senior adults at home - Rivas Costa,Carlos; Fernández Iglesias,Manuel José; Anido Rifón,Luis Eulogio; Gómez Carballa,Miguel; Valladares Rodríguez,Sonia (PeerJ, 2017)
Introduction The computing capabilities of state-of-the-art television sets and media centres may facilitate the introduction of computer-assisted evaluation at home. This approach would help to overcome the drawbacks of traditional pen-and-paper evaluations administered in clinical facilities, as they could be performed in a more comfortable environment, the subject’s home, and they would be more flexible for designing complex environments for the evaluation of neuropsychological constructs that are difficult to assess through traditional testing. The objective of this work was to obtain some initial evidence about the technical acceptance by senior adults of serious games played at home on the TV set and therefore about the convenience of further investigating such an approach to cognitive assesment. Materials and Methods We developed a collection of games to be deployed on a TV environment. These games were tried by a group of senior adults at their homes. The Technology Acceptance Model (TAM) was used to validate this approach. Surveys were performed to study the perceived usefulness and perceived ease of use of such technical setting as an instrument for their cognitive evaluation; that is, its technical acceptance. Subjective information collected from participants was correlated with actual interaction data captured. An additional survey was performed 36 months after pilot testing to have an indication about the long-term perceptions about usefulness and ease of use. Results More than 90% of participating subjects perceived cognitive games on TV as useful or very useful. The majority of participants selected the TV set as their preferred option to interact with serious games at home, when compared to other devices such as smartphones, tablets or PCs. This result correlates with the number of participants perceiving them as easily usable or very easy to use, and also with automatically captured interaction data. Three out of four seniors expressed their interest in keeping the system at home after the pilot. Besides, these perceptions are fairly stable in time as shown by the survey performed 36 months after pilot testing. Limitations Although participating users are a representative sample of the Galician population, which in turn is comparable to the population of most rural areas in Europe, a larger and more diverse user sample would be needed to obtain significant results for a wider population profile. Conclusion The study confirmed the technical acceptance, that is, the perceived usefulness and perceived ease of use, of the TV-based home technical setting introduced as a means of cognitive evaluation. This study provides initial evidence on the viability of a TV-based serious games approach for cognitive longitudinal screening at home with little intervention of clinical professionals, thus contributing to the early detection of cognitive impairments in the senior population.
Keywords: Serious games; Senior adults; Cognitive evaluation; In-home care; Smart TV; Acceptability studies